Multidrug-resistant Proteus mirabilis in a critically endangered Malayan pangolin: clinical and genomic insights - Chen, Ziqiao; Wang, Jiayi; Wang, Kai; An, Fuyu; Liu, Shasha; Yan, Haikuo; Hua, Yan (Frontiers in Veterinary Science, 2025)
Proteus mirabilis, an important zoonotic opportunistic pathogen, is widely found in nature and the intestinal tracts of animals, which can cause diarrhea, pneumonia, urinary tract infections, and other symptoms in domestic animals including sheep, pigs, cattle and chickens. In this study, necropsy of a deceased critically endangered Malayan pangolin revealed lobar pneumonia in the lungs and hepatocyte necrosis with hepatic cord disintegration in the liver. A strain of Proteus mirabilis (PM2022) was isolated from the affected lungs and liver. This bacterium exhibited multidrug resistance, being susceptible only to cefoxitin and amikacin. Whole-genome sequencing identified 26 antibiotic resistance genes, including CTX-M-65, FosA3, which mediate resistance to five classes of antibiotics, such as penicillins and quinolones. Additionally, 20 virulence factors (including the T6SS secretion system, hemolysins HpmA/B, among others) were detected. Mouse experiments confirmed its high pathogenicity (LD50 = 1.45 × 109 CFU/mL). Based on experimental and genomic testing results, the initial symptoms of Proteus mirabilis infection in pangolins manifest in the lungs, liver, and intestines, and the use of penicillins and quinolones should be avoided during treatment. This study offers clinical guidance for diagnosing and treating P. mirabilis infections in pangolins, informing evidence-based antimicrobial strategies.